2012
DOI: 10.1155/2012/789572
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Manifestations in Cystic Fibrosis

Abstract: Cystic fibrosis is a genetic disease, characterized by accumulation of thickened mucous secretions in exocrine glands. Although the major clinical manifestations of the disease are pancreatic and pulmonary disease, the majority of cystic fibrosis patients will develop sinonasal manifestations as well. This paper outlines the etiology, evaluation, and management of the nasal and sinus manifestations in patients with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 60 publications
1
28
0
12
Order By: Relevance
“…In children, findings such as demineralised bilateral uncinate processes and medial displacement of the lateral nasal wall in the CT of paranasal sinuses should raise the suspicion of CF 6. The CT scan of the paranasal sinuses in patients with CF, however, invariably shows anatomical alteration when compared with the non-CF population 14 25.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In children, findings such as demineralised bilateral uncinate processes and medial displacement of the lateral nasal wall in the CT of paranasal sinuses should raise the suspicion of CF 6. The CT scan of the paranasal sinuses in patients with CF, however, invariably shows anatomical alteration when compared with the non-CF population 14 25.…”
Section: Discussionmentioning
confidence: 99%
“…The CT scan of the paranasal sinuses in patients with CF, however, invariably shows anatomical alteration when compared with the non-CF population 14 25. Fortunately, there is no proven correlation between image findings with the chronic rhinosinusitis disease severity 6 9 14. Interestingly, one study has shown an inverse correlation between the endoscopic and the CT findings of the sinuses with the CF disease severity score, the Shwachman and Kulczycki scoring system 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal irrigations, nasal steroids, antibiotic courses, nebulized antibiotics, chest physiotherapy, and exercises aid to clear the copious secretions and thwart infections [96]. …”
Section: Managementmentioning
confidence: 99%
“…Nasal irrigations, nasal steroids, antibiotic courses, nebulized antibiotics, chest physiotherapy, and exercises aid to clear the copious secretions and thwart infections [96]. (4) Immunodeficiencies.…”
Section: 1mentioning
confidence: 99%